Gonadotropin independent sexual precocity in a Pakistani male infant from an activating mutation in LHCGR gene - Ayesha Shahid; Noor Ibrahim, Mohsina (Journal of the Pakistan Medical Association, 2023)
A male child, aged seven months, visited the out patients clinic of the National Institute of Child Health, Karachi, in May 2020 with the features of iso-sexual puberty. After ruling out the more common causes of early puberty, like congenital adrenal hyperplasia and tumours secreting chorionic gonadotropin hormone, hormonal assessment indicated raised testosterone independent of gonadotropin. The volume of the testicles was symmetric and testicular ultrasonography revealed no mass. Genetic analysis for the LHCGR gene was performed for confirmation which revealed activating heterozygous missense pathogenic mutation in c.1732G>T (p.Asp578Tyr). This is the first reported case of testotoxicosis (FMPP) from Pakistan which was genetically confirmed. Keywords: Testosterone, Puberty, Gonadotrophins, Mutation, Genetic.